Understanding company law (Thomson Legal and Regulatory Australia, 2008)
These amandments includes : reducing the regulatory burden on provides of financial services; simplifying company reporting obligations; improving auditor independence rules; removing unnecessary member approval requirements in relation to small transactions; facitlitating funddraisings